2018
DOI: 10.31015/jaefs.18034
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil yield and compositions of sage (Salvia Officinalis L.) cultivated in different province of Turkey

Abstract: Salvia officinalis is known as sage or garden sage. Salv a comes from the Lat n salveo and salvaro, terms that mean "save" and "cure." (Anonymus, 2018). Sage is a perennial plant rich in volatile oil belonging to Lamiaceae family. The genus Salvia, belonging to Lamiaceae,are represented by over 900 species worldwide. Anatolia is a major centre for Salvia in Asia, 47 of its 90 species endemic to Turkey (Kan et al, 2007). The sage is a herbaceous or bushy plant that can be grow up to 60-100 cm, and the flowers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The 4 major component were eucalyptol (1,8-cineole) (27.08%), thujone (20.52%), camphor (16.99%), beta-pinene (4.07%). Other authors have reported sage essential oil with a comparable composition although there are some differences regarding the quantity of the individual compounds (Kırıcı et al, 1996;Delamare et al, 2007;Said-Al Ahl et al, 2015;Craft et al, 2017;Khedler et al, 2017;Çelik et al, 2018;Karik et al, 2018). The rosemary essential oil isolated was mainly composed of five compounds: eucalyptol (26.36%), camphor (29.17%), borneol (7.34%), alpha pinene (6.72%) camphene (4.95%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 major component were eucalyptol (1,8-cineole) (27.08%), thujone (20.52%), camphor (16.99%), beta-pinene (4.07%). Other authors have reported sage essential oil with a comparable composition although there are some differences regarding the quantity of the individual compounds (Kırıcı et al, 1996;Delamare et al, 2007;Said-Al Ahl et al, 2015;Craft et al, 2017;Khedler et al, 2017;Çelik et al, 2018;Karik et al, 2018). The rosemary essential oil isolated was mainly composed of five compounds: eucalyptol (26.36%), camphor (29.17%), borneol (7.34%), alpha pinene (6.72%) camphene (4.95%) in this study.…”
Section: Discussionmentioning
confidence: 99%